Trend fundamentals and exchange rate dynamics - Florian Huber; Daniel Kaufmann (University of Salzburg, Department of Social Sciences and Economics, 2019)
We estimate a multivariate unobserved components stochastic volatility model to explain the dynamics of a panel of six exchange rates against the US Dollar. The empirical model is based on the assumption that both countries' monetary policy strategies may be well described by Taylor rules with a time-varying inflation target, a time-varying natural rate of unemployment, and interest rate smoothing. Compared to the existing literature, our model simultaneously provides estimates of the latent components included in a typical Taylor rule specification and the model-based real exchange rate. Our estimates closely track major movements along with important time series properties of real and nominal exchange rates across all currencies considered, outperforming a benchmark model that does not account for changes in trend inflation and trend unemployment. More precisely, the proposed approach improves upon competing models in tracking the actual evolution of the real exchange rate in terms of simple correlations while it appreciably improves upon simpler competitors in terms of matching the persistence of the real exchange rate.
Keywords: F31; E52; F41; C5; E31; 330; exchange rate models; trend inflation; natural rate of unemployment; Taylor rule; unobserved components stochastic volatility model